2019
DOI: 10.1155/2019/8131052
|View full text |Cite
|
Sign up to set email alerts
|

Rotation Stiffness Investigation of Spatial Joints with End‐Plate Connection

Abstract: Spatial joints with end-plate connections show significant spatial coupling effects under spatial loading. Mechanical behaviour and failure modes of these spatial joints differ from those of planar joints. This study involved experiments and finite element analyses with respect to planar joints with end-plate connections under static load. The numerical results agreed well with the experimental data, and this verified the adequacy of the finite element analyses. Then, finite element models of the spatial inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…While Grimsmo, E.L. et al [ 14 ] studied the dynamic loading conditions and found that the ductility of the end-plate joints was improved. Chen, S. et al [ 15 ] proposed a stiffness calculation formula suitable for spatial joints by improving the EC3 component method. Stiffness calculation difference between plane joints and spatial joints connected by the end-plate were compared.…”
Section: Introductionmentioning
confidence: 99%
“…While Grimsmo, E.L. et al [ 14 ] studied the dynamic loading conditions and found that the ductility of the end-plate joints was improved. Chen, S. et al [ 15 ] proposed a stiffness calculation formula suitable for spatial joints by improving the EC3 component method. Stiffness calculation difference between plane joints and spatial joints connected by the end-plate were compared.…”
Section: Introductionmentioning
confidence: 99%